PENGGUNAAN METODE PEMBELAJARAN OUTDOOR STUDY TERHADAP PEMAHAMAN KONSEP PELESTARIAN LINGKUNGAN HIDUP PESERTA DIDIK DI MTsN SINGAPARNA - Kurniangsih, Alien; Darsiharjo, Darsiharjo; Maryani, Enok (Universitas Pendidikan Indonesia, 2015)
In an era of globalization of environmental sustainability issues into one focus of attention. All components agreed to lift the attitude and wisdom in the environment that need to transfer knowledge through educational institutions. Understanding the form of the values in the learning process needs to be passed on to each generation. On that basis, the study was conducted under the title